Perancangan Data Warehouse Sistem Pendaftaran Mahasiswa Menggunakan Online Analytical Procesing (OLAP) di Universitas Ma’soem - Muhamad Fahmi Nugraha; Muhamad Furqon (INTERNAL (Information System Journal), 2021)
Along with the development of Information Technology in various fields, one of which is Education can be seen from various existing systems, one of which is the Student Registration System which is increasingly advanced, no longer manually but using an Information System, of course this information system is not only used as a registration information system. of course there are data that can still be processed. Based on the data obtained from the information system, higher education institutions can analyze registrant data. This study aims to produce an information system that can be used by universities to analyze new student data by designing the Online Analytical Processing (OLAP) Data Warehouse. The results of writing using this Information System can help universities to analyze data, furthermore it can be used as decision making, strategic information to reports